Transformasi Sektor Keuangan dengan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan SKPD (Kajian Persepsi Auditor terhadap Pemerintah Kepulauan Bangka Belitung) - Marheni, Marheni; Maharani, Yunita; Irwansyah, Robby (Scientia: Jurnal Hasil Penelitian, 2023)
This study aims to analyze the financial transformation with HR competence on the financial quality of the Kepulauan Bangka Belitung Government SKPD based on the auditor's perception. This is studied by analyzing the influence of HR competence on the perception of the quality of financial reports produced by the financial report manager of the Kepulauan Bangka Belitung Province SKPD. This research is an explanatory research. The population in this study were 50 people in Kepulauan Bangka Belitung Province. Financial auditors conduct employee assessments in finance and planning as SKPD financial report makers. Data analysis techniques using SEM. The results showed that based on the auditor's perception, knowledge had a significant effect on the perception of the quality of financial statements. Expertise has no significant effect on perceived quality of financial statements. Attitude has a significant effect on the perception of the quality of financial statements. Based on the results of the HR competency test consisting of knowledge and attitudes that affect the perception of the quality of the SKPD's financial reports. Meanwhile, expertise/skills have no significant effect on the perception of the quality of financial reports